2015
DOI: 10.1007/s00408-015-9754-2
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse Idiopathic Pulmonary Neuroendocrine Cell Hyperplasia (DIPNECH) and the Role of Somatostatin analogs: A Case Series

Abstract: From our single institution review of neuroendocrine pulmonary tumor cases, we found only five cases of DIPNECH, which reaffirms rare nature of the pathology. It primarily affects females over 60 years with dry cough as the most common presenting symptom. Most of our patients responded to treatment with a somatostatin analog and had significant improvement in their presenting symptoms. Somatostatin analogs were well tolerated resulting in significant resolution of presenting symptoms in most of our patients. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 19 publications
1
16
0
Order By: Relevance
“…Octreotide, a somatostatin analogue shown to reduce the hormonal hypersecretion of neuroendocrine cells in gastrointestinal and bronchial carcinoids [46], has been used with some success, particularly in the presence of somatostatin receptors [47]. CHAUHAN and RAMIREZ [47] retrospectively evaluated five cases of DIPNECH among 184 cases of primary pulmonary neuroendocrine tumours and observed significant improvement of symptoms (cough) in four patients treated with somatostatin analogues. Similar results have recently been reported by CARR et al [21].…”
Section: Management and Prognosismentioning
confidence: 99%
“…Octreotide, a somatostatin analogue shown to reduce the hormonal hypersecretion of neuroendocrine cells in gastrointestinal and bronchial carcinoids [46], has been used with some success, particularly in the presence of somatostatin receptors [47]. CHAUHAN and RAMIREZ [47] retrospectively evaluated five cases of DIPNECH among 184 cases of primary pulmonary neuroendocrine tumours and observed significant improvement of symptoms (cough) in four patients treated with somatostatin analogues. Similar results have recently been reported by CARR et al [21].…”
Section: Management and Prognosismentioning
confidence: 99%
“…To date, there were four case series reported regarding the SSAs therapy in patients with DIPNECH syndrome. These studies reported significant improvement or even complete regression of the respiratory symptoms (especially cough) in almost all patients treated with SSAs [8,9,13,15].…”
Section: Discussionmentioning
confidence: 96%
“…The clinical course however, is characterized by slowly progressive, unspecific pulmonary symptoms such as long-lasting dry cough, wheezing and exertional dyspnoea [2,[4][5][6][7][8]. Nonetheless, DIPNECH can also cause severe airflow obstruction and respiratory failure which can prove fatal [2,3,7,9].…”
Section: Abbreviationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lung neuroendocrine tumours (NETs) are classified according to their pathological characteristics (Table 1) [2]. Diffuse idiopathic pulmonary neuroendocrine cell hyperplasia (DIPNECH) is considered a pre-invasive lesion with a potential toward the development of lung NETs [3,4]. Lung carcinoids (LC) are rare tumours [5]; however, incidence is increasing due to improvement in diagnostic techniques [6].…”
Section: Introductionmentioning
confidence: 99%